Muslims and the making of modern Europe - Greble, Emily, 1978- (New York, NY)
xv, 354 sayfa
Keywords: “Muslims and the Making of Modern Europe shows that Muslims were citizens of modern Europe from its beginning and, in the process, rethinks Europe itself. Muslims are neither newcomers nor outsiders in Europe. In the twentieth century, they have been central to the continent's political development and the evolution of its traditions of equality and law. From 1878 into the period following World War II, over a million Ottoman Muslims became citizens of new European states. In Muslims and the Making of Modern Europe, Emily Greble follows the fortunes and misfortunes of several generations of these indigenous men, women and children; merchants, peasants, and landowners; muftis and preachers; teachers and students; believers and non-believers from seaside port towns on the shores of the Adriatic to mountainous villages in the Balkans. Drawing on a wide range of archives from government ministries in state capitals to madrasas in provincial towns, Greble uncovers Muslims' negotiations with state authorities—over the boundaries of Islamic law, the nature of religious freedom, and the meaning of minority rights. She shows how their story is Europe's story: Muslims navigated the continent's turbulent passage from imperial order through the interwar political experiments of liberal democracy and authoritarianism to the ideological programs of fascism, socialism, and communism. In doing so, they shaped the grand narratives upon which so much of Europe's fractious present now rests. Muslims and the Making of Modern Europe offers a striking new account of the history of citizenship and nation-building, the emergence of minority rights, and the character of secularism“ --